2017
DOI: 10.1139/cjpp-2017-0036
|View full text |Cite
|
Sign up to set email alerts
|

Effects of kisspeptin on diabetic rat platelets

Abstract: Hyperglycemia, hyperlipidemia, and free radicals result in platelet activation and atherogenesis. Kisspeptin (KP) is able to regulate metabolism, hemostasis, and the development of atherosclerosis. We examined whether platelet aggregation of streptozotocin-induced diabetic rats depends on the inducer type and if KP-13 and RF-9 (a kisspeptin receptor modifier) can influence platelet function. We measured the speed and the maximum of aggregation, along with the area under the curve. Serum glucose and calcium lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 55 publications
1
12
1
Order By: Relevance
“…None of the ligands significantly altered the STZ-induced increase in serum glucose concentration and decreased body weight gain ( Table 1 ), indicating they were unable to restore the STZ-induced metabolic changes. Consistent with our previous study [ 42 ], we found elevated serum cholesterol, ALT and urea levels in the STZ-induced diabetic animals, which may be explained by the hepatic and renal toxic effects of STZ [ 37 , 38 ]. The STZ-induced rise in serum ALT concentration was further boosted by the S1R ligands, although the growth was not significant for PRE-084 ( Fig 1 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…None of the ligands significantly altered the STZ-induced increase in serum glucose concentration and decreased body weight gain ( Table 1 ), indicating they were unable to restore the STZ-induced metabolic changes. Consistent with our previous study [ 42 ], we found elevated serum cholesterol, ALT and urea levels in the STZ-induced diabetic animals, which may be explained by the hepatic and renal toxic effects of STZ [ 37 , 38 ]. The STZ-induced rise in serum ALT concentration was further boosted by the S1R ligands, although the growth was not significant for PRE-084 ( Fig 1 ).…”
Section: Discussionsupporting
confidence: 92%
“…These results suggest the metabolism and/or elimination of ligands in the liver or kidney [ 43 ]. The platelet count below the reference value [ 44 ], already observed in our previous study, can be explained by reduced thrombopoietin production due to the liver and kidney damage associated with STZ-induced diabetes [ 42 ]. However, in the present study, we only observed a trend towards a decrease in platelet counts in the STZ-treated animals compared to the vehicle-treated, healthy rat group, which was normalized by PRE-084 and NE-100.…”
Section: Discussionmentioning
confidence: 76%
“…The platelet count below the reference value, 30 already observed in our previous studies, could be explained by reduced thrombopoietin production due to the liver and kidney damage associated with STZ-induced diabetes. 39 Sub-chronic treatment with S1R ligands had, no effect on platelet formation, although this is not relevant in the present study as eicosanoid synthesis was monitored at a standard platelet count (2.5×10 8 platelets/μL) (Table 1) .…”
Section: Discussionmentioning
confidence: 80%
“…Platelets primarily produce the vasoconstrictor thromboxane, which induces platelet aggregation, and the endothelium primarily produces the vasodilator prostacyclin, which inhibits platelet aggregation, but under physiological conditions these products are in equilibrium to ensure normal local circulation. 31,39,44…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation